Pathogenesis of giant cell arteritis with focus on cellular populations - Stamatis, Pavlos; Turesson, Carl; Michailidou, Despina; Mohammad, Aladdin J. (Frontiers in Medicine, 2022)
Giant cell arteritis (GCA), the most common non-infectious vasculitis, mainly affects elderly individuals. The disease usually affects the aorta and its main supra-aortic branches causing both general symptoms of inflammation and specific ischemic symptoms because of the limited blood flow due to arterial structural changes in the inflamed arteries. The pathogenesis of the GCA is complex and includes a dysregulated immune response that affects both the innate and the adaptive immunity. During the last two decades several studies have investigated interactions among antigen-presenting cells and lymphocytes, which contribute to the formation of the inflammatory infiltrate in the affected arteries. Toll-like receptor signaling and interactions through the VEGF-Notch-Jagged1 pathway are emerging as crucial events of the aberrant inflammatory response, facilitating among others the migration of inflammatory cells to the inflamed arteries and their interactions with the local stromal milieu. The increased use of checkpoint inhibitors in cancer immunotherapy and their immune-related adverse events has fed interest in the role of checkpoint dysfunction in GCA, and recent studies suggest a dysregulated check point system which is unable to suppress the inflammation in the previously immune-privileged arteries, leading to vasculitis. The role of B-cells is currently reevaluated because of new reports of considerable numbers of plasma cells in inflamed arteries as well as the formation of artery tertiary lymphoid organs. There is emerging evidence on previously less studied cell populations, such as the neutrophils, CD8+ T-cells, T regulatory cells and tissue residing memory cells as well as for stromal cells which were previously considered as innocent bystanders. The aim of this review is to summarize the evidence in the literature regarding the cell populations involved in the pathogenesis of GCA and especially in the context of an aged immune system.